The Role of Religion in the Formation of the Identity of the Aur Birugo Community of Bukittinggi City - Wahid, Annisa; Rahim, Rahimin Affandi Abdul (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2024)
This research aims to explore the role of religion, particularly Islam, in shaping the identity of the Aur Birugo community in Bukittinggi Regency. We employed a qualitative research method, utilizing in-depth interviews, participatory observation, and document analysis as tools to gather data. The results of the research indicate that religion, specifically Islam, has a significant impact on shaping the identity of the Aur Birugo community. Religious values such as honesty, social care, and solidarity have become integral parts of the community's social norms. Religious institutions like mosques and Islamic boarding schools play a crucial role in educating the younger generation and preserving religious traditions. Traditional ceremonies and religious celebrations are also inseparable aspects of the Aur Birugo community's culture. While religion has played a vital role in maintaining the community's cultural identity, this research also identifies challenges in facing inter-religious conflicts and the influence of modern social changes. In adapting to the changing times, the Aur Birugo community continues to strive to preserve their religious and cultural roots while adapting to the dynamics of a rapidly evolving global society. This research contributes to understanding how religion serves as a strong social bond while dealing with the dynamics of social and cultural development in Bukittinggi Regency.